Karakteristik Sifat Fisis Biobriket Limbah Tongkol Jagung dan Serbuk Kayu : Physical Properties Characteristics of Corn Cob and Wood Dust Waste Biobriquettes - Wulandari, Febriana; Lestari, Dini (HUTAN TROPIKA, 2024)
This research uses corncob waste and wood dust as raw materials. The amount of corn cob waste and sawdust is quite large, thus supporting the availability of raw materials. The biomass waste used in this research is corn cob waste and wood dust. The composition of corn cob fiber is 23.74% lignin, 65.96% cellulose, and 10.82% hemicellulose. Wood powder contains hemicellulose between 27.51 - 35.88%, a-cellulose between 43.15-48.73%, lignin between 22.73-33.60%. High lignin content has the potential to produce high calorific value. This research aims to determine the physical properties of corn cob and wood powder biomass waste briquettes, determine the quality standards for corn cob charcoal and wood powder briquettes based on the SNI 01-6235-2000 standard and compare the values ​​with standards from Japan, America and England and determine the feasibility based on the results of testing the physical properties of charcoal briquettes. The research method used was an experimental method with a non-factorial Completely Randomized Design (CRD) and three replications. Based on the SNI 01-6235-2000 standard, corncob charcoal briquettes meet the standard, while the calorific value for sawdust does not meet the standard. The ANOVA test results showed that the treatment had a significant effect on ash content, calorific value, bound carbon content, volatile matter content and had no significant effect on water content. Corn cob charcoal briquettes are suitable for use as charcoal briquette fuel because all physical properties meet SNI standards.